2017
DOI: 10.1097/ico.0000000000001176
|View full text |Cite
|
Sign up to set email alerts
|

Two-Year Clinical Outcome of 500 Consecutive Cases Undergoing Descemet Membrane Endothelial Keratoplasty

Abstract: Clinical outcomes remain excellent up to 2 years after DMEK, in particular for eyes operated on for FECD and with completely attached grafts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
65
8
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(91 citation statements)
references
References 31 publications
8
65
8
4
Order By: Relevance
“…The postoperative endothelial cell density (ECD) serves as an indirect reference for the potential longevity of the DMEK graft. Reports about the postoperative ECD after DMEK vary in the literature as do the different learning curves of the individual surgeon (Price et al 2009;Deng et al 2017;Peraza-Nieves et al 2017).…”
Section: Worldwidementioning
confidence: 99%
“…The postoperative endothelial cell density (ECD) serves as an indirect reference for the potential longevity of the DMEK graft. Reports about the postoperative ECD after DMEK vary in the literature as do the different learning curves of the individual surgeon (Price et al 2009;Deng et al 2017;Peraza-Nieves et al 2017).…”
Section: Worldwidementioning
confidence: 99%
“…Aynı zamanda sütür sorunlarının olmaması ve hızlı korneal iyileşme gibi avantajları bulunmaktadır. 17 DMEK ile daha iyi görsel sonuçlar bildirilmekle birlikte, ameliyat sonrası DSEAK cerrahisine göre daha fazla oranda ÖK'ye hava enjeksiyonu ihtiyacı rapor edilmiştir. 18 Ameliyat sonrası dönemde greft ayrılması nedeniyle, ÖK'ye hava enjeksiyonu oranlarını %3-73 gibi çok geniş bir aralıkta bildirilen çalışmalar mevcuttur.…”
Section: Discussionunclassified
“…18 Ameliyat sonrası dönemde greft ayrılması nedeniyle, ÖK'ye hava enjeksiyonu oranlarını %3-73 gibi çok geniş bir aralıkta bildirilen çalışmalar mevcuttur. 17,[19][20][21] Ancak, DMEK cerrahisinde tecrübe artıkça ve uygun vakaların seçilmesi ile bu oranlar düşmektedir. Çalışmamızda, tüm olguların %10,3'ünde greft ayrılması nedeniyle tekrar hava enjeksiyonu gerekmiş ve bu oran literatür ile uyumlu bulunmuştur.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…[14][15][16] Among different EK techniques, Descemet's membrane endothelial keratoplasty (DMEK) is the most advanced technique because of its ultrathin graft, extremely low rejection rate, better visual recovery, and minimal immunosuppressive regime usage. 17 One study comprising 1000 consecutive DMEK cases showed the rejection rate was only 0.9% in 1 year and 2.3% in 4 years, 18 whereas another study reported the rejection rate of Descemet's stripping automated endothelial keratoplasty (DSAEK) was 4.8% within 3 years. 19 The advantages of DMEK imply the technique might be a promising direction for future xeno-corneal transplantation.…”
Section: Introductionmentioning
confidence: 99%